Motivasi Sains Mahasiswa dalam Pembelajaran Konsep Dasar IPA Fisika melalui Virtual Laboratory - Duwi Nuvitalia; Ernawati Saptaningrum; Siti Patonah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The purpose of this study was to determine the students' scientific motivation in learning, especially practical activities in learning the Basic Concepts of Science Physics through a virtual laboratory. The method used in this study is a survey research conducted on second semester students of elementary school teacher candidates. The instrument used is the Science Motivation Questionnaire II with a Likert scale of 1-5. The science motivation questionnaire consists of five components including intrinsic motivation, self-determination, self-efficacy, career motivation, and motivation grade. The results showed that the science motivation of students who took the Basic Concepts of Science Physics course as a whole was in the category of often to always motivated as much as 62.77%. Meanwhile, for the occasional to often motivated category as much as 33.11% and the rarely to sometimes category as much as 2.13%. The highest scientific motivation indicator is on the motivation grade indicator, while the lowest category is on the self-determination indicator.